Identification of Readiness to Participate in The Teacher Professional Program Chemistry Education Students - Retnowulan, Sri Rahayu; Rosdalina, Rosdalina; Damanik, Irma Rezeki; Mellyzar, Mellyzar; Chairani, Riza Chourulliah; Rauzah, Rauzah (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to find out how prepared Malikussaleh University Chemistry Education students are in participating in the Professional Teacher Program (PPG) in order to become professional teachers. The type of research used in this research is quantitative descriptive. The subjects of this research were 29 alumni of Chemistry Education students at Malikussaleh University class 2015-2019, with techniques is probability sampling. Meanwhile, the object studied is readiness to take part in PPG with the six aspects reviewed, including: health aspects, interest aspects, motivation aspects, family environment aspects, socio-economic aspects and campus environmental aspects. The data collection technique in this research uses an instrument in the form of a questionnaire. Data analysis techniques use descriptive statistics with the help of applications Microssoft  Excel. And the results obtained from research on readiness to participate in PPG are that the health aspect has a percentage of 89% (very good), then the interest aspect has a percentage of 73% (good), then there is the motivation aspect which has a percentage of 53% (fair), then the family environment aspect which has a percentage of 77% (good), then the socio-economic aspect which has a percentage of 70% (good), and finally the campus environmental aspect which has a percentage of 68% (good). Based on the research results, it can be concluded that readiness to take part in the Professional Teacher Program is to become a professional teacher in the good category with an average percentage of these six aspects of 72%.